Photometric and structural parameters of newly discovered nuclear star clusters in Local Volume galaxies - Hoyer, Nils; Neumayer, Nadine; Seth, Anil C; Georgiev, Iskren Y; Greene, Jenny E (Monthly notices of the Royal Astronomical Society, 2023)
We use high-resolution Hubble Space Telescope imaging data of dwarf galaxies in the Local Volume (⁠≲11Mpc⁠) to parameterize 19 newly discovered nuclear star clusters (NSCs). Most of the clusters have stellar masses of Mnsc⋆≲106M⊙ and compare to Galactic globular clusters in terms of ellipticity, effective radius, stellar mass, and surface density. The clusters are modelled with a Sérsic profile and their surface brightness evaluated at the effective radius reveals a tight positive correlation to the host galaxy stellar mass. Our data also indicate an increase in slope of the density profiles with increasing mass, perhaps indicating an increasing role for in situ star formation in more massive hosts. We evaluate the scaling relation between the clusters and their host galaxy stellar mass to find an environmental dependence: for NSCs in field galaxies, the slope of the relation is α=0.82+0.08−0.08 whereas α=0.55+0.06−0.05 for dwarfs in the core of the Virgo cluster. Restricting the fit for the cluster to Mgal⋆≥106.5M⊙ yields α=0.70+0.08−0.07⁠, in agreement with the field environment within the 1σ interval. The environmental dependence is due to the lowest-mass nucleated galaxies and we speculate that this is either due to an increased number of progenitor globular clusters merging to become an NSC, or due to the formation of more massive globular clusters in dense environments, depending on the initial globular cluster mass function. Our results clearly corroborate recent results in that there exists a tight connection between NSCs and globular clusters in dwarf galaxies.
Gesehen am 24.04.2023